Design of an Android-Based Motorcycle Service Booking Application - Farizqi, Muhammad Ridwan; Kalifia, Anna Dina; Sejati, Rr.Hajar Puji (International Journal Software Engineering and Computer Science (IJSECS), 2024)
A motorbike is a two-wheeled vehicle powered by an engine. Motorbike users are required to service their cars because the components on the motorbike will experience a decrease in performance along with the length of time they use the motorbike. However, this can be overcome by servicing your motorbike regularly. However, sometimes motorbike users have to face queues at workshops that are long and quite time-consuming. Then, an Android-based online motorbike service booking system was created, which did not require customers to come to the seminar directly to make a booking. With this application, customers must book via Android by selecting the desired schedule. The application was created using Android Studio with the Kotlin programming language. The database section uses the Firebase Real-time Database to update the data in real-time. The service provider will also easily confirm orders via the website connected to Firebase. In short, it is hoped that this application can help motorbike users book services online so they don't have to spend time queuing.